2013
DOI: 10.1002/mrd.22273
|View full text |Cite
|
Sign up to set email alerts
|

trans‐10, cis‐12 conjugated linoleic acid enhances in vitro maturation of porcine oocytes

Abstract: The aim of this study was to determine the effects of trans-10, cis-12 conjugated linoleic acid (t10c12 CLA) supplementation on oocyte maturation and embryo development in pigs. Compared with the control, supplementation of 50 µM t10c12 CLA to in vitro maturation (IVM) medium significantly increased the proportion of oocytes at the metaphase-II (MII) stage and subsequent parthenogenetic embryo development in terms of cleavage rate, blastocyst formation rate, and cell numbers in blastocysts. The t10c12 CLA-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…We also selected a JAK inhibitor to disrupt JAK/STAT3 signaling because JAK is the key kinase responsible for the activation of STAT3. According to dose–response experiments done previously by our lab and others (Liu et al, ; Marei et al, ; Nguyen et al, ; Jia et al, ), we pretreated cultured bovine COCs with 10 µM U0126 or 5 µM JAK inhibitor, and then measured levels of phosphorylated MAPK (p‐MAPK3/1) or STAT3 (p‐STAT3). Adding U0126 or JAK inhibitor significantly reduced the relative levels of p‐MAPK3/1 or p‐STAT3 compared to total MAPK3/1 and STAT3 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also selected a JAK inhibitor to disrupt JAK/STAT3 signaling because JAK is the key kinase responsible for the activation of STAT3. According to dose–response experiments done previously by our lab and others (Liu et al, ; Marei et al, ; Nguyen et al, ; Jia et al, ), we pretreated cultured bovine COCs with 10 µM U0126 or 5 µM JAK inhibitor, and then measured levels of phosphorylated MAPK (p‐MAPK3/1) or STAT3 (p‐STAT3). Adding U0126 or JAK inhibitor significantly reduced the relative levels of p‐MAPK3/1 or p‐STAT3 compared to total MAPK3/1 and STAT3 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various nutrients, metabolites, and substrates are transported through gap junction between cumulus cells and oocytes for sucessful maturation (Li et al, 2015). And several genes including PTX3, GJA1, and PTGS2 are involved with cumulus expansion and function of gap junction in mammalian oocytes (Zhang et al, 2005; Jia et al, 2014; Li et al, 2015). In present study, although treatment of 50 µM ALA enhanced cumulus expansion at 22 h after maturation, GJA1 mRNA in cumulus cells was downregulated at 44 h after maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of GJA1 mRNA by ALA was similar with results of FA metabolism-related genes. Jia et al (2014) reported that trans-10, cis-12 conjugated linoleic acid (t19c12 CLA) promoted protein expression of cyclo-oxygenase 2 (COX2; also known as PTGS2) in porcine oocytes for 22 h after maturation, whereas it was not differed at 44 h. These findings lead to predict that ALA treatment during first 22 h of maturation would promote FAs metabolism and gap junction for transport and production of energy, however, these are supressed to maintain energy balance during 22 h after first maturarion period. Therefore, our futher plan include invastigation of cumulus expansion-related genes and cAMP levels during first 22 h in IVM.…”
Section: Discussionmentioning
confidence: 99%
“…The level of GSH in each blastocyst was measured with 10 μmol/L 4-chloromethyl-6.8-difluoro-7-hydroxycoumarin (Cell-Tracker Blue) with a filter at 370 nm excitation. The experimental procedure was same as the ROS measurement described above [ 23 ].…”
Section: Methodsmentioning
confidence: 99%